The Evolutionary Origin of Peroxisomes: An ER-Peroxisome Connection - Agatha Schlüter; Stéphane Fourcade; Raymond Ripp; Jean‐Louis Mandel; Olivier Poch; Aurora Pujol (2006)
The peroxisome is an essential eukaryotic organelle, crucial for lipid metabolism and free radical detoxification, development, differentiation, and morphogenesis from yeasts to humans. Loss of peroxisomes invariably leads to fatal peroxisome biogenesis disorders in man. The evolutionary origin of peroxisomes remains unsolved; proposals for either a symbiogenetic or cellular membrane invagination event are unconclusive. To address this question, we have probed with a peroxisomal proteome, an "ensemble" of 19 representative eukaryotic complete genomes. Molecular phylogenetic and sequence comparison tools allowed us to identify four proteins as peroxisomal markers for unequivocal in silico peroxisome detection. We have then detected the Apicomplexa phylum as the first group of organisms devoid of peroxisomes, in the presence of mitochondria. Finally, we deliver evidence against a prokaryotic ancestor of peroxisomes: (1) the peroxisomal membrane is composed of purely eukaryotic bricks and is thus useful to trace the eukaryotes in their evolutionary paths and (2) the peroxisomal matrix protein import system shares mechanistic similarities with the endoplasmic reticulum/proteasome degradation process, indicating a common evolutionary history.